Mineralized Biofertilizers in Agroecological Systems: Microbial Interactions and Challenges for Production Scaling - Trejo-Ibarra, Oneyda; Vargas-Arispuro , Irasema; Quintana-Obregón, Eber Addí; Sánchez-Chávez, Esteban; Aispuro-Hernández, Emmanuel; Martínez-Téllez, Miguel Ángel (REVISTA TERRA LATINOAMERICANA, 2025)
The deterioration of agricultural soils, characterized by the progressive reduction in nutrient availability, organic matter, and the loss of soil structure and populations of beneficial microorganisms, represents a critical challenge that threatens food security due to its adverse ef fects on crop production and the sustainability of agricultural systems. In this context, the implementation of agroecological practices emerges as a key strategy for soil preservation and restoration. Agroecology, as a discipline, integrates ecological principles to design sustainable food systems that operate in harmony with nature, minimizing dependence on chemical inputs that negatively af fect ecosystems. Among agroecological strategies, the use of mineralized biofertilizers stands out as a promising alternative for restoring the soil microbiome, improving plant nutrition, and promoting environmentally friendly agricultural systems. These biofertilizers contain beneficial microorganisms, such as nitrogen-fixing, cellulose-degrading, and siderophore-producing bacteria, that establish symbiotic interactions with plants and the surrounding soil environment. These interactions contribute to key processes such as nutrient mineralization and solubilization, enhancing the uptake and assimilation of essential macro- and micronutrients by crops. The objective of this review is to compile and analyze the agroecological potential of mineralized biofertilizers in plant nutrition and the restoration of degraded soils, with emphasis on their production techniques, the beneficial microorganisms involved, and their reported agronomic benefits in various crops. To this end, a bibliographic search was conducted in scientific databases such as Scopus, Web of Science, PubMed, Google Scholar, SciELO, and Redalyc, covering publications in Spanish and English from the last 15 years, with a focus on experimental studies, systematic reviews, and technical and regulatory literature related to agroecological practices and mineral biofertilization.